Plasmodium vivax chloroquine resistance links to pvcrt transcription in a genetic cross - Juliana M. Sá; Sarah R. Kaslow; Roberto R. Moraes Barros; Nicholas F. Brazeau; Christian M. Parobek; Dingyin Tao; Rebecca E. Salzman; Tyler J. Gibson; Soundarapandian Velmurugan; Michael A. Krause; Viviana Melendez-Muniz; Whitney A. Kite; et al. (Nature Communications, 2019)
Here, a cross of Plasmodium vivax malaria parasites links a chloroquine resistance (CQR) phenotype to a 76 kb region of chromosome 1 and greater expression of pvcrt, an ortholog of the Plasmodium falciparum CQR transporter gene.